Electronic Effects of Linker Substitution on Lewis Acid Catalysis with Metal-Organic Frameworks - Vermoortele, Frederik; Vandichel, Matthias; Van de Voorde, Ben; Ameloot, Rob; Waroquier, Michel; Van Speybroeck, Veronique; De Vos, Dirk E. (Angewandte Chemie International Edition, 2012)
Functionalized linkers can greatly increase the activity of metal–organic framework (MOF) catalysts with coordinatively unsaturated sites. A clear linear free‐energy relationship (LFER) was found between Hammett σm values of the linker substituents X and the rate kX of a carbonyl‐ene reaction. This is the first LFER ever observed for MOF catalysts. A 56‐fold increase in rate was found when the substituent is a nitro group (see picture).